Speech-in-Noise Perception in Children With Cochlear Implants, Hearing Aids, Developmental Language Disorder and Typical Development: The Effects of Linguistic and Cognitive Abilities - Torkildsen, Janne von Koss; Hitchins, Abigail; Myhrum, Marte; Wie, Ona Bø (Frontiers in Psychology, 2019)
Children with hearing loss, and those with language disorders, can have excellent speech recognition in quiet, but still experience unique challenges when listening to speech in noisy environments. However, little is known about how speech-in-noise perception relates to individual differences in cognitive and linguistic abilities in these children. The present study used the Norwegian version of the Hearing in Noise Test (HINT) to investigate speech-in-noise perception in 175 children aged 5.5-12.9 years, including children with cochlear implants (CI, n = 64), hearing aids (HA, n= 37), developmental language disorder (DLD, n = 16) and typical development (TD, n= 58). Further, the study examined whether general language ability, verbal memory span, nonverbal IQ and speech perception of monosyllables and sentences in quiet were predictors of performance on the HINT. To allow comparisons across ages, scores derived from age-based norms were used for the HINT and the tests of language and cognition. There were significant differences in speech-in-noise perception between all the groups except between the HA and DLD groups, with the CI group requiring the highest signal-to-noise ratios (i.e. poorest performance) and the TD group requiring the lowest signal-to-noise ratios. For the full sample, language ability explained significant variance in HINT performance beyond speech perception in quiet. Follow-up analyses for the separate groups revealed that language ability was a significant predictor of HINT performance for children with CI, HA and DLD, but not for children with TD. Memory span and IQ did not predict variance in speech-in-noise perception when language ability and speech perception in quiet were taken into account. The finding of a robust relation between speech-in-noise perception and general language skills in all three clinical groups call for further investigation into the mechanisms that underlie this association.